Peak width of skeletonized mean diffusivity (PSMD) as neuroimaging biomarker for vascular cognitive impairment in the context of cerebral amyloid angiopathy - Zotin, Maria Clara Zanon (2022)
Introduction - An unmet need in the field of cerebral small vessel diseases (cSVDs) is how to measure the widespread white matter (WM) injury that underlies vascular cognitive impairment in a feasible and clinically meaningful way. Though conventional MRI markers play a pivotal role in diagnosing cSVD, they are less sensitive to subtle changes in the normal-appearing white matter and yield generally weak and inconsistent cognitive associations. The quest for the ideal MRI marker to fit the critical role of a reliable outcome measure in large clinical trials has become a research priority in the field, and the future development of disease-modifying therapies depends on it. A recently developed diffusion-based metric, called peak width of skeletonized mean diffusivity (PSMD), aligns with current scientific needs and priorities. It was specifically designed to quantify the burden of cSVD and reflect related cognitive impairment in a fast and automated way. Nonetheless, knowledge about PSMD is still limited in the scientific community, and data on its utility in the context of CAA, the second most common form of sporadic cSVD, is scarce. Objectives: We set out to critically evaluate PSMD\'s role as neuroimaging biomarker for vascular cognitive impairment and investigate its potential applications in CAA. Methods: To this end, we conducted three research projects. First, we performed a systematic review to gather and synthesize the evidence supporting PSMD\'s role as a biomarker in the context of cSVD and other WM disorders. Then, we conducted a cross-sectionally investigation on PSMD\'s neuroimaging and cognitive associations in patients with CAA and mild cognitive impairment. Finally, we expanded on previous research by investigating PSMD\'s regional variations in CAA, while comparing its neuroimaging and cognitive associations with other conventional diffusion-based MRI markers. Based on these three articles, we critically discuss the generalizability of our results, the challenges related to applying PSMD in Brazilian samples, and the measures that can be taken to advance clinical translation. Results: Several key findings emerge from our investigations. PSMD is on a fast track towards validation as a surrogate for cognitive endpoints in VCI, but full validation depends on further technical and longitudinal studies. In CAA, PSMD shows strong and consistent neuropsychological associations, outperforming other conventional and diffusion-based MRI markers. Compared to mean diffusivity and fractional anisotropy, PSMD presents specific neuroimaging correlates and stronger cognitive associations, underscoring an increased sensitivity to clinically relevant microstructural disruption. Furthermore, we found that the degree to which PSMD values decrease from posterior to anterior regions is higher among probable-CAA compared to non-CAA subjects, indicating more severe WM microstructural damage in the posterior areas of the brain, which is consistent with several histopathologic and neuroimaging studies. Conclusions: Our results support PSMD\'s promising role as a marker of global/regional WM injury and related cognitive decline in the context of CAA and other WM diseases.